Cotton and fiber quality in function of picker harvest speed - Kazama, Elizabeth H. [UNESP]; Silva, Rouverson P. da [UNESP]; Ormond, Antonio T. S.; Alcantara, Aline S. [UNESP]; Vale, Welington G. do (Univ Federal Campina Grande, 2018)
Cotton price is determined by the quality of the fiber, which can be damaged at the time of harvest, in addition to quantitative losses of non-harvested plume, Therefore, this study aimed to analyse soil and plant losses, and the quality of cotton fiber in relation to five harvest speeds (5, 6, 7, 8, and 9 km h(-1)) in the spindle system (picker). The experiment was conducted in Lucas do Rio Verde, Mato Grosso, Brazil. A randomized complete block design was used on plots of 0.9 ha, with 20 plot, five speeds, and four blocks. The results showed that the studied speeds did not significantly influence losses on the soil and plant, or the quality of the cotton fiber; therefore, the highest speed may be recommended.
Keywords: picker; spindles system; fiber characteristics; Gossypium hirsutum